Dampak Positif dari Perdagangan Nasional - Lubis, Mutia Putri Nabila; Harahap, Mhd Ikhsan (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
The role that comes from conducting international trade is to help influence the economic development of every nation. By carrying out international trade and the payment problems that occur in it will be able to have an influence on development in two opposite paths and even lead to separation. By creating various possibilities for specialization and income through other methods that are much more productive so that they can trigger changes in foreign countries. The advantages of the high value of natural resources will provide a process through trade routes that will accelerate the development of the Indonesian nation.